The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1152/jn.00500.2017
|View full text |Cite
|
Sign up to set email alerts
|

TRPC5 is required for the NO-dependent increase in dendritic Ca2+and GABA release from chick retinal amacrine cells

Abstract: GABAergic signaling from amacrine cells (ACs) is a fundamental aspect of visual signal processing in the inner retina. We have previously shown that nitric oxide (NO) can elicit release of GABA independently from activation of voltage-gated Ca channels in cultured retinal ACs. This voltage-independent quantal GABA release relies on a Ca influx mechanism with pharmacological characteristics consistent with the involvement of the transient receptor potential canonical (TRPC) channels TRPC4 and/or TRPC5. To deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
(85 reference statements)
2
11
0
Order By: Relevance
“…The higher magnitude of change NO-dependent cytosolic Ca 2+ in zero Ca 2+ external is due to the lower resting cytosolic Ca 2+ level (normal external, 1,808 ± 131.7 AU; n = 45; zero Ca 2+ external, 1,460 ± 94.2 AU; n = 54; p < 0.05, unpaired t -test, Figure 1G ). The decay time constant in normal external was larger than that in zero Ca 2+ external condition, suggesting that the later part of the response was more dependent upon extracellular Ca 2+ , consistent with activation of TRPC5 (Maddox et al, 2018 ; normal external, 213.8 ± 22.9, n = 33 s; zero Ca 2+ external, 45.8 ± 6.2 s, n = 49; p < 0.0001, unpaired t -test, Figure 1H ). Together, these results suggest that NO-bubbled solutions can elicit both Ca 2+ influx across the plasma membrane and release of Ca 2+ from internal stores.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…The higher magnitude of change NO-dependent cytosolic Ca 2+ in zero Ca 2+ external is due to the lower resting cytosolic Ca 2+ level (normal external, 1,808 ± 131.7 AU; n = 45; zero Ca 2+ external, 1,460 ± 94.2 AU; n = 54; p < 0.05, unpaired t -test, Figure 1G ). The decay time constant in normal external was larger than that in zero Ca 2+ external condition, suggesting that the later part of the response was more dependent upon extracellular Ca 2+ , consistent with activation of TRPC5 (Maddox et al, 2018 ; normal external, 213.8 ± 22.9, n = 33 s; zero Ca 2+ external, 45.8 ± 6.2 s, n = 49; p < 0.0001, unpaired t -test, Figure 1H ). Together, these results suggest that NO-bubbled solutions can elicit both Ca 2+ influx across the plasma membrane and release of Ca 2+ from internal stores.…”
Section: Resultssupporting
confidence: 54%
“…1G). The decay time constant in normal external was larger than that in zero Ca 2+ external condition, suggesting that the latter part of the response was more dependent upon extracellular Ca 2+ , consistent with activation of TRPC5 (Maddox et al, 2018;normal external, 213.8 ± 22.9 s, n = 33; zero Ca 2+ external, 45.8 ± 6.2 s, n = 49; p < 0.0001, unpaired t-test, Figure 1H). Together, these results suggest that NO-bubbled solutions can elicit both Ca 2+ influx across the plasma membrane and release of Ca 2+ from internal stores.…”
Section: No Releases Ca 2+ From Storessupporting
confidence: 67%
See 1 more Smart Citation
“…In chick ACs in vitro, NO transiently reverses GABA-and glycine-gated currents, converting inhibition of ACs into excitation, thereby increasing the firing of these cells and thus enhanced inhibitory drive on their synaptic partners (e.g., RGCs). This NO-induced shift in E Cl− is likely due to release of Cl − from intracellular stores (Hoffpauir et al, 2006;Krishnan and Gleason, 2015;Krishnan et al, 2017;Maddox and Gleason, 2017;Maddox et al, 2018). In addition, NO may drive synaptic glutamate release from BCs without membrane depolarization via a TRPC Ca 2+ influx-mediated pathway, as shown in the chick retina (Maddox et al, 2018), further depolarizing ACs.…”
Section: Why Do Amacrine Cells Become Hyperactive? a Hypothesismentioning
confidence: 89%
“…The involvement of SVs in the NOdrCl is especially relevant to AC function because ACs participate in serial [ 74 ] and reciprocal synapses [ 21 ] such that presynaptic Cl - can affect the sign of nearby incoming GABAergic synapses in a highly localized fashion [ 22 24 ]. We have also recently demonstrated that the NO donor SNAP can increase spontaneous and evoked GABA release via presynaptic activation of TRPC5 channels [ 41 , 75 ] providing an additional NO-dependent mechanism for enhancing GABAergic output from ACs.…”
Section: Discussionmentioning
confidence: 99%